(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
This article explores the historical and structural development of groups of related languages, tracing how languages within a family have diverged and evolved from a common ancestral language over time.By examining phonological, syntactical, and lexical changes, linguists uncover connections and patterns within and across language groups, providing insights into human prehistory, migration patterns, and sociocultural transformations. This study highlights how languages change, split, or merge over generations, illustrating the dynamic and interconnected nature of human languages across the globe.